Kesenjangan Sosial Sebagai Ide Penciptaan Karya Seni Lukis Surealis - Muhammad Fahrey Todi; Lisa Widiarti (Jurnal Riset Rumpun Seni, Desain dan Media, 2024)
In a residential neighborhood, there are often significant differences in the level of welfare between one neighbor and another. Several factors such as income, employment, access to public services, and available facilities can contribute to social disparities between them. Planning a housing complex with various types of houses. In a complex there are several families who have very good economic conditions and are able to meet their living needs quite comfortably. However, on the other hand, there are also other families who experience financial difficulties and are unable to meet their basic needs.